Depth-color based 3D image transmission over wireless networks with QoE provisions - Song, Zhe (2013)
The deployment of 3-D image techniques is one of the most promising fields among the development of new applications for natural image scenes. Driven by urgent demands from industry and users, 3-D image technology has received significant research attention in recent years. 3D image streaming gives users an extra dimension of visual sense that greatly improves the liveliness and joyfulness of user experience. However, they also raise new challenges (e.g., bandwidth and energy efficiency) especially in achieving satisfactory Quality of Experience (QoE) performances. QoE has become critical multimedia quality metrics determining whether a potential multimedia application or service is successful or not. In this paper, we propose a QoE-driven wireless 3D image transmission scheme with depth-color source coding adaptations according to the wireless network conditions. Specifically, our contribution includes: (1) developing a patch-pixel based source coding scheme for 3D image transmission; (2) proposing a 3D image quality model; (3) and developing a quality-driven 3D image transmission approach based on the quality model. Experimental results demonstrate that the proposed techniques can significantly improve the QoE of 3D image over wireless networks.